A computational study of water mobility on smooth surface, cavities and porous structure with hydrophilic and hydrophobic coatings / Yong Kok Wee - Yong , Kok Wee (2020)
This research focus on water mobility and discovers a new phenomenon where droplet accelerates on a hydrophilic cavity surface when sliding down from a hydrophobic surface. The kinetic energy of droplet increases six (6) times higher than before sliding into the first cavity. This finding is useful for creating an effective way of filling liquids into cavities for passive microfluidics related devices. The work consists of validating cases using Computational Fluid Dynamics (CFD) software. The first part of the research reviews the literature regarding CFD modelling of a water droplet (i) sliding down on a surface, (ii) detachment in a gas-flowed microchannel and (iii) jumping upon coalescence on a superhydrophobic surface. Then, this research continues with the investigations regarding the water retention behaviour in porous structures, i.e., an ideal structure and an actual porous metal structure, and further investigates the effect of different static contact angles and liquid drainage rates in a reservoir for each type of porous structures. Also, this research develops a method to quantify additional parameters for porous metal i.e., the structural homogeneity and the number of junctions besides the other parameters like pores per inch and porosity. With that, the present research able to relate the structural variations and its effect on the distribution of water saturation in the porous structures. In details, it detects the presence of large pores in the porous metal geometry, i.e., two times larger than the small pores that reduces the capacity in retaining water.